Radio controlled quadcopter with augmented range and control for special missions requiring live data and video transmission - Sivanathan, K; Chandreshbhai Gajjar, Romin; Kumar Kar, Sanjaya (International Journal of Engineering and Technology, 2018)
Recently, the natural and man-made calamities have been observed erratically with solutions provided majority of times being born by military and other rescue teams which is often a time-consuming process. This project focuses on such remote operations like surveillance of buildings, calamities hit areas by first understanding its behavior and later on have a platform for the others to enact by using the live data transmission on the Ground Station which can be a Computer, or any display networking device. The Flight Control also consists of 10 DOF IMU embedded along with the Microcontroller in order to stabilize the entire System. The scope of this project is to stabilize the semi-autonomous control system of an Unmanned Aerial Vehicle (UAV) for remote operations through live video data along with various parameters and sensor readings with real time graph plots generated and the location is updated on Google maps.The initial step was to make a complete design of the Quad Copter on Solid Works with which real time mechanical simulations were achieved. Then the state space equation of quadcopter was derived by using Processing Software. Subsequently the link budget calculation, attainment of the PID gain values and real time Data Transmission of Video feed on finite number of computer and networking devices, real time sensor graphs and GPS location on Google Maps were implemented. Finally, the quadcopter was tested for some special applications.Â
Keywords: Quad Copter; Augmented Range; Remote Operation; Data Transmission.